Analysis of microbial growth in a fermented sausage and risk evaluation of its production - Östling, Marcus (SLU/Department of Molecular Sciences, 2018)
Fermentation has been used to enhance safety of foods and prolong its shelf lives for a long time. The fermentation was originally a result of spontaneous fermentation by microbes naturally present in the food, it is currently done by addition of known bac-teria in a starter culture.